2015
DOI: 10.4088/pcc.15r01821
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin Therapy in Psychiatric Disorders

Abstract: Further research is required to better clarify the benefit of gabapentin in psychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 98 publications
0
49
0
4
Order By: Relevance
“…However, a placebo‐controlled trial in panic disorder patients failed to distinguish gabapentin and placebo . As of 2015, there were no published randomized, controlled trials evaluating the efficacy of gabapentin in GAD …”
Section: Gabapentinoids In Anxiety Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a placebo‐controlled trial in panic disorder patients failed to distinguish gabapentin and placebo . As of 2015, there were no published randomized, controlled trials evaluating the efficacy of gabapentin in GAD …”
Section: Gabapentinoids In Anxiety Disordersmentioning
confidence: 99%
“…It is widely prescribed off‐label for diabetic neuropathy and other neuropathic pain conditions. Numerous other off‐label and investigational uses for gabapentin have been described, including alcohol dependence, bipolar disorder, posttraumatic stress disorder, essential tremor, and perioperative anxiety . Pregabalin, approved for clinical use in the United States in 2004, is indicated for postherpetic neuralgia and partial‐onset seizures, and for the treatment of diabetic neuropathy, fibromyalgia, and neuropathic pain associated with spinal cord injury.…”
mentioning
confidence: 99%
“…17 Other trials of gabapentin in anxiety have focused on preoperative anxiety and have mostly found gabapentin to be more effective than placebo. 11 Given the lack of evidence of efficacy of gabapentin in bipolar disorder and anxiety, it may be difficult to understand the widespread prescription of the drug for these off-licence indications. However, the pharmaceutical company which promoted gabapentin, Pfizer, has been fined in the USA for illegal promotion of gabapentin for unlicenced indications.…”
Section: It Wasmentioning
confidence: 99%
“…These findings suggest that possible pathology of the reward circuitry in response to ethanol use can be remedied through potentiation of I h currents. Thus, while LTG is useful for treatment of bipolar disorder, the benefit of gabapentin seems limited to anxiety and alcohol dependence [270]. Further research is required to conclusively define a role for gabapentin and LTG in other psychiatric disorders.…”
Section: Therapeutic Potential Of Hcn Channelsmentioning
confidence: 99%